2007
DOI: 10.1111/j.1600-0897.2007.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Platelet‐Activating Factor on the Secretion of Interleukin‐8 and Growth‐Regulated Oncogene α in Human Immortalized Granulosa Cell Line (GC1a)

Abstract: Our data indicated that IL-8 and GROalpha were regulated by C-PAF. The results suggested that PAF may play an important role in human pre-ovulatory processes involving IL-8 and GROalpha production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On the basis of present observations, IL-8 and GROα in FF are thought to lead to neutrophil chemoattraction and accumulation. As our results also indicated that IL-8 and GROα are regulated by a mechanism involving TNF-α, it is likely that IL-8 and GROα may play an important role in the accumulation of neutrophils and in the subsequent induction of ovulation [ 33 ]. It has been suggested that IL-8 and GROα may be important modulators of preovulatory events, not only by attracting and activating neutrophils that will eventually play a role in timely follicular rupture, but also by stimulating new blood vessel formation for the corpus luteum [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of present observations, IL-8 and GROα in FF are thought to lead to neutrophil chemoattraction and accumulation. As our results also indicated that IL-8 and GROα are regulated by a mechanism involving TNF-α, it is likely that IL-8 and GROα may play an important role in the accumulation of neutrophils and in the subsequent induction of ovulation [ 33 ]. It has been suggested that IL-8 and GROα may be important modulators of preovulatory events, not only by attracting and activating neutrophils that will eventually play a role in timely follicular rupture, but also by stimulating new blood vessel formation for the corpus luteum [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our previous results also indicated that IL-8 and GRO-α are upregulated by IL-1α, TNF-α [31] and platelet-activating factor [32] in GC1a, IL-8 and GRO-α may play an important role in the accumulation of leukocytes and subsequent induction of ovulation. Moreover, our data also show that the production of IL- 8 and GRO-α is decreased by treatment with U0126, a MEK inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-8 and GRO-α are induced by inflammatory cytokines or a lipid mediator such as platelet-activating factor from GC1a [31,32]. …”
Section: Methodsmentioning
confidence: 99%
“…Amounts of basal IL-8 in the ovary are low, but production increases in granulosa cells and theca cells upon LH stimulation [11]. IL-8 is also known to increase vascular permeability [19, 20], which may facilitate the infiltration process. In addition, the infiltrating leukocytes may interact with ovarian endothelial cells and other cell types via a multitude of chemokines during ovulation [2123].…”
Section: Trafficking Of Leukocytes Into the Ovarymentioning
confidence: 99%